Dynamic taxonomy generation for future skills identification using a named entity recognition and relation extraction pipeline - Gonzalez-Gomez, Luis Jose; Hernandez-Munoz, Sofia Margarita; Borja, Abiel; Arana-Salas, Fernando A.; Azofeifa, Jose Daniel; Noguez, Julieta; Caratozzolo, Patricia (Frontiers in Artificial Intelligence, 2025)
IntroductionThe labor market is rapidly evolving, leading to a mismatch between existing Knowledge, Skills, and Abilities (KSAs) and future occupational requirements. Reports from organizations like the World Economic Forum and the OECD emphasize the need for dynamic skill identification. This paper introduces a novel system for constructing a dynamic taxonomy using Natural Language Processing (NLP) techniques, specifically Named Entity Recognition (NER) and Relation Extraction (RE), to identify and predict future skills. By leveraging machine learning models, this taxonomy aims to bridge the gap between current skills and future demands, contributing to educational and professional development.MethodsTo achieve this, an NLP-based architecture was developed using a combination of text preprocessing, NER, and RE models. The NER model identifies and categorizes KSAs and occupations from a corpus of labor market reports, while the RE model establishes the relationships between these entities. A custom pipeline was used for PDF text extraction, tokenization, and lemmatization to standardize the data. The models were trained and evaluated using over 1,700 annotated documents, with the training process optimized for both entity recognition and relationship prediction accuracy.ResultsThe NER and RE models demonstrated promising performance. The NER model achieved a best micro-averaged F1-score of 65.38% in identifying occupations, skills, and knowledge entities. The RE model subsequently achieved a best micro-F1 score of 82.2% for accurately classifying semantic relationships between these entities at epoch 1,009. The taxonomy generated from these models effectively identified emerging skills and occupations, offering insights into future workforce requirements. Visualizations of the taxonomy were created using various graph structures, demonstrating its applicability across multiple sectors. The results indicate that this system can dynamically update and adapt to changes in skill demand over time.DiscussionThe dynamic taxonomy model not only provides real-time updates on current competencies but also predicts emerging skill trends, offering a valuable tool for workforce planning. The high recall rates in NER suggest strong entity recognition capabilities, though precision improvements are needed to reduce false positives. Limitations include the need for a larger corpus and sector-specific models. Future work will focus on expanding the corpus, improving model accuracy, and incorporating expert feedback to further refine the taxonomy.